KONFLIK ANTARA INDUSTRI PENGOLAHAN IKAN DAN MASYARAKAT DI DESA PENGAMBENGAN KECAMATAN NEGARA KABUPATEN JEMBRANA - Buana Putra, Putu Tegar (Humanis, 2014)
This study tries to examine the phenomenon of conflict involving the fish processing industry and the community in the village of Pengambengan, State District, Jembrana regency. Problems in this study focused on the root causes of conflict, conflict and forms of conflict resolution is done with the fish processing industry communities. There are two theories that are used to explore the research problem is Conflict Theory by Lewis Coser about the safety valve as well as the conflicts realistic and non-realistic. Reciprocity theory is used to examine the relationship between community Pengambengan and fish processing industries. This study uses qualitative descriptive-qualitative analysis. Conflicts between communities and the fish processing industry in the village Pengambengan caused by environmental pollution factors by fish processing industries such as marine water pollution, soil and air, further jealousy factor between the community and the fish processing industry in the village Pengambengan, and the factor of competition between the processing industry fish in the Village Pengambengan. Form of conflict in the village Pengambengan covering protests from villagers Pengambengan due to environmental pollution, the write-off action is performed by the youths Pengambengan, action of throwing the fish processing industry, then being rejected by the supply of fish from outside the village community Pengambengan. The conflict resolution chosen by the public and the fish processing industry negotiations.
Keywords: Fish Processing Industries, Conflict, Environmental Pollution